PENGUATAN PEMAHAMAN KEAGAMAAN DAN LITERASI KEUANGAN REMAJA DI KAWASAN EKS LOKALISASI BANDAR BARU - Bagus Ramadi; Sri Wulandari; Syahla Nabila; Besty Aprilia; Alifia Haira Harahap (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The former Bandar Baru red-light district is a region that faces social challenges, especially for teenagers growing up in a dynamic and diverse community. Low levels of religious understanding and financial literacy are among the factors influencing their behavior and lifestyle. This community service program aims to strengthen religious understanding and financial literacy among teenagers through a collaborative educational outreach model between Gatra Adiwangsa Community Service Program (KKN) students from the State Islamic University of North Sumatra and the BOPTN-PkM program from the State Islamic University of North Sumatra. The activities were carried out through several sessions, including the Love, Pride, Understand the Rupiah (CBPR) socialization program, the Care, Recognize, Complain (PEKA) program, an introduction to the QRIS digital payment system, and religious outreach themed "Strengthening Teenagers' Religious Understanding as an Effort to Prevent Free Sex in the Bandar Baru Red-light District." The educational outreach method implemented encouraged the active participation of students from MTS YPI Al-Hilal Bandar Baru and the surrounding community through discussions, questions and answers, and simple simulations. The results of the activities showed an increase in teenagers' understanding of religious values ​​and awareness of Sharia-based financial literacy. This program represents a concrete step by universities to strengthen the character and independence of youth in socially vulnerable areas through a synergy between spiritual and financial education. Keywords: educational counseling; religious understanding; financial literacy; youth; Bandar Baru